Genetic variation of morphological and yield-related traits in backcrossed and selfed population of maize - Saha, Iman; Rathinavel, Krishnakumar; Manoharan, Bharani; Karthikeyan, Adhimoolam; Sampathrajan, Vellaikumar; Rajasekaran, Ravikesavan; Raveendran, Muthurajan; Senthil, Natesan (Journal of Phytology, 2022)
The number of genes controlling the morphological and yield-related traits and their mode of action plays a vital role in selecting traits and favourable progenies in a segregating population. In this study, we analysed the skewness and kurtosis in the backcrossed and selfed populations of SC11-2×UMI1230β1+. Negative skewness refers to redundant gene activity, positive skewness is connected to complementary gene action. Positive kurtosis suggests the existence of gene activity controlled by a smaller number of genes. Negative kurtosis shows a lack of gene activity and is controlled by a large number of genes. The BC2F2 population of plant height and single plant yield showed positive skewness and platykurtic distribution, suggesting that the genes were governed by complementary gene action and controlled by the large number of genes. This implied need for rigorous selection to achieve a genetic gain in later generations. Cob length and kernel weight showed a duplicate gene action which implied that mild selection can fix these traits and accelerate genetic gain.